Real-world data studies in oncology: analysis of the Russian publications - V. F. Achikyan; A. A. Kurylev; A. S. Kolbin (Реальная клиническая практика: данные и доказательства)
Background. Real-world data studies are an important source of knowledge on malignant tumors and their treatment. This knowledge is a tool for making decisions by health care professionals and patients. Regarding this, authors conducted literature search to identify real-world data studies published in the Russian scientific journals.Objective. The study aim was finding and analyzing publications on real-world evidence studies in oncology therapeutic area.Materials and methods. Full-text articles published in the Russian peer-reviewed medical scientific journals of 2022 and 2023 were systematically relieved and analyzed.Results. 119 publications were selected. The following types of study data were identified: 1) data on patients management practice; 2) survival and other oncology outcomes regardless of treatment approach; 3) survival and other oncology outcomes depending on treatment approach; 4) efficacy of a concrete therapy; 5) treatment safety (toxicity) data; 6) clinical and demographic prognostic factors; 7) tumor (morphological, molecular and genetic) prognostic factors; 8) tumor characteristics (morphological, molecular and genetic) regardless of their prognostic significance; 9) oncology disease characteristic (e. g., comorbidities) regardless of its prognostic significance. The most common types of study data were the following: clinical and demographic prognostic factors — 24 studies; tumor (morphological, molecular and genetic) prognostic factors — 36 studies; tumor characteristics (morphological, molecular and genetic) regardless of their prognostic significance — 38 studies.Conclusion. The modern real-world data studies in oncology therapeutic area are a very important source of knowledge on malignant tumors and their treatment.